2014
DOI: 10.1073/pnas.1403255111
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of beak and feather disease virus across a host ring-species complex

Abstract: Pathogens have been hypothesized to play a major role in host diversity and speciation. Susceptibility of hybrid hosts to pathogens is thought to be a common phenomenon that could promote host population divergence and subsequently speciation. However, few studies have tested for pathogen infection across animal hybrid zones while testing for codivergence of the pathogens in the hybridizing host complex. Over 8 y, we studied natural infection by a rapidly evolving single-strand DNA virus, beak and feather dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 53 publications
(84 reference statements)
4
62
1
Order By: Relevance
“…The carotenoid-rich oil droplets found in the retinas of all birds, lungfish and many reptiles (Goldsmith et al, 1984;Vorobyev, 2003;Walls, 1942) are also a potential source of intraspecific variation in visual sensitivity, because the density of pigments in these droplets is known to be affected by external variables such as diet (Bowmaker et al, 1993;Knott et al, 2010) and ambient light intensity (Hart et al, 2006). However, comparisons of morphs and subspecies of varying plumage coloration (Eastwood et al, 2014) have so far not revealed systematic differences in visual sensitivity (Knott et al, 2012(Knott et al, , 2013, even when the species has intraspecific variation in acoustic and visual signals Ribot et al, 2009Ribot et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…The carotenoid-rich oil droplets found in the retinas of all birds, lungfish and many reptiles (Goldsmith et al, 1984;Vorobyev, 2003;Walls, 1942) are also a potential source of intraspecific variation in visual sensitivity, because the density of pigments in these droplets is known to be affected by external variables such as diet (Bowmaker et al, 1993;Knott et al, 2010) and ambient light intensity (Hart et al, 2006). However, comparisons of morphs and subspecies of varying plumage coloration (Eastwood et al, 2014) have so far not revealed systematic differences in visual sensitivity (Knott et al, 2012(Knott et al, , 2013, even when the species has intraspecific variation in acoustic and visual signals Ribot et al, 2009Ribot et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…The nest boxes used in this study are of a typical design, construction and placement for nest boxes in Australia and elsewhere and are commonly occupied by small‐ to medium‐sized birds such as rosellas (Berg & Ribot ; Eastwood et al . ; Mihailova et al . ; Larson et al .…”
Section: Methodsmentioning
confidence: 99%
“…During this period, CRP were by far the most common mammal to occupy nest boxes at this site, but CBPs also occurred. This timing was chosen to avoid interference with rosella reproduction in the nest boxes, which is monitored as part of other studies (Eastwood et al., , ; Knott et al., ; Larson et al., ; Mihailova et al., ; Ribot et al., ).…”
Section: Methodsmentioning
confidence: 99%